2023
DOI: 10.1007/s11269-022-03399-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Daily Reference Evapotranspiration from Climate Variables: Assessment of Bagging and Boosting Regression Approaches

Abstract: The increasing frequency of droughts and floods due to climate change has severely affected water resources across the globe in recent years. An optimal design for the scheduling and management of irrigation is thus urgently needed to adapt agricultural activities to the changing climate. The accurate estimation of reference crop evapotranspiration (ET0), a vital hydrological component of the water balance and crop water need, is a tiresome task if all the relevant climatic variables are unavailable. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The PM model was used as the reference model in this study, and various ML models based on LR, RF, NN, SVM, etc., were developed to estimate ET 0 with limited climatic variables and their combinations as input parameters. The study findings align with previous research studies, which suggested that high prediction accuracy can be achieved by incorporating all the climatic parameters in the models (Ayaz et al., 2021; Elbeltagi et al., 2022; Jayashree et al., 2023). However, according to Alves et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The PM model was used as the reference model in this study, and various ML models based on LR, RF, NN, SVM, etc., were developed to estimate ET 0 with limited climatic variables and their combinations as input parameters. The study findings align with previous research studies, which suggested that high prediction accuracy can be achieved by incorporating all the climatic parameters in the models (Ayaz et al., 2021; Elbeltagi et al., 2022; Jayashree et al., 2023). However, according to Alves et al.…”
Section: Discussionsupporting
confidence: 91%
“…Under the limited availability of all the parameters, the effectiveness of the PM method remains compromised in determining ET 0 as in the case of CROPWAT 8.0 software, which provides average wind velocity data, which does not vary in months, and thus software computes ET 0 either under/over in the absence of actual wind speed data for a given location. ML algorithms have the capability of handling real-time massive data to accurately estimate ET 0 (Jayashree et al, 2023;Kim et al, 2022), particularly in locations where data are scarce. As a result, the purpose of this work is to assess ML techniques for estimating ET 0 with limited climatic inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our model boasts the highest Rsquared values (0.98-0.99), which indicates a very strong correlation between predicted and observed EV T 0 values. While Tr et al [16] achieved a lower RMSE (0.016), their results may not be directly comparable due to potentially limited data scope or specific application. Compared to other studies (Hill et al [9], Hu et al [12], Dong et al [18]), our approach demonstrates significantly lower and more consistent RMSE and MAE values across a wider range, which suggests greater generalizability and accuracy.…”
Section: Results Comparisonmentioning
confidence: 83%
“…However, the FAO-PM method is not without limitations. The main disadvantage of the FAO-PM method is the need for numerous input data, which are often not available at meteorological sites [19][20][21], especially in developing countries such as Bosnia and Herzegovina (BiH) [19] or other regions [22]. When the data are available, they are often inaccurate due to poor maintenance of meteorological sites and sensors, especially those for solar radiation, humidity, and windspeed measurement [23].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies in which different methods were tested against the Penman-Monteith method, and the results were dependent on climatic conditions and the specific site location, the period of observation and the type of data (daily, monthly) used for the ET o estimate, and the site elevation as well as seaside vicinity [19][20][21][22][23][24][25]. The remarkable development of artificial intelligence in recent years has enabled researchers to acquire large data sets with non-linear relationships between various climatic variables to accurately predict ET o [21]. Models such as ANNs (Artificial Neural Networks), ELMs (Extreme Learning Machines), SVMs (Support Vector Machines), ANFISs (Adaptive Neuro-Fuzzy Inference Systems), etc.…”
Section: Introductionmentioning
confidence: 99%